Issues that support the creation of ICT workarounds: towards a theoretical understanding of feral information systems. (1st September 2016) - Spierings, Anthony; Kerr, Don; Houghton, Luke
Abstract: enterprise system (ES) software is often supplemented independently by end users who develop personal solutions that establish connections between the required business practices and the ES. One solution is a type of information and communications technology workaround, a feral information system (FIS) – defined as a workaround designed to achieve certain requirements by using any information technology tool that an end user uses in conjunction with, or instead of, the mandated information system. To explore this, we conducted a case study at a large utility company. We conclude that feral information systems are not a behavioural deviance. FISs are by‐products of end users seeking operational efficiency, namely, to nullify additional transactional costs imposed by the ES. Our findings suggest that end users of ES will fall into one of four modes of operation: mode 1, where end users submit to the ES; mode 2, where they dismiss the ES; mode 3, where they develop an FIS that remains hidden from the ES proponents; and mode 4, where they operate the FIS in open defiance of the ES proponents. In this research, we deliberately take the practitioner view and, therefore, outline how different pressures help to create an FIS as a response to a poorly mandated ES. We also make a theoretical contribution by exploring issues that lead to workarounds and suggest that future research into these modes of operation can be theorized in future proposed studies.